TWO GENERAL FIXED POINT RESULTS ON WEAK PARTIAL METRIC SPACE - Durmaz, G.; Acar, Ö.; Altun, I. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
In this work, we obtain two fixed point results on weak partial metric space. Our results are extend and generalize some previous results.